2013
DOI: 10.1208/s12249-013-9998-1
|View full text |Cite
|
Sign up to set email alerts
|

Correction for Irrelevant Absorption in Multicomponent Spectrophotometric Assay of Riboflavin, Formylmethylflavin, and Degradation Products: Kinetic Applications

Abstract: Abstract. In the spectrophotometric assay of multicomponent systems involved in drug degradation studies, some minor or unknown degradation products may be present. These products may interfere in the assay and thus invalidate the results due to their absorption in the range of analytical wavelengths. This interference may be eliminated by the application of an appropriate correction procedure to obtain reliable data for kinetic treatment. The present study is based on the application of linear and non-linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It is hydrolyzed to LC and LF [1819 2233] and is oxidized to CMF [20,27,32]. Both LC and LF are also sensitive to light, with LC having relatively better stability [36].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…It is hydrolyzed to LC and LF [1819 2233] and is oxidized to CMF [20,27,32]. Both LC and LF are also sensitive to light, with LC having relatively better stability [36].…”
Section: Reviewmentioning
confidence: 99%
“…It has been suggested that the formation of the β-keto acid and the flavo-violet type compounds takes place through a 1,2-dihydro-1-methyl-2-oxo-quinoxaline-3-carboxyureide intermediate in the reaction [164]. The presence of similar compounds in the hydrolytic degradation of formylmethylflavin in alkaline media has been reported [33]. Earlier studies on the alkaline hydrolysis of FMF showed the formation of LC and LF by the cleavage of the formyl side chain [19,22].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations